Notes from the Underground - Editors, The (Pomegranate, 1999)
According to Edward Whitmont, in Return of the Goddess (NY: Crossroads, 1989), our newfound interest in the magical and the matrifocal is causing material which has long laid dormant in our unconscious to now be brought to the surface. For the most part this is a good thing, but Whitmont cautions us that the “free-floating impulses from the magical layer are powder charges waiting to be ignited by the sparks from the torches of the returning Dionysos and his menadic retinue”. Many of us seem to be aware of this, at least intuitively, and are concerned about the implied potential for violence in Nature Religion and Neopaganism, especially about their fringes.